Ecology and Phenotypic Variations of Vitellaria Paradoxa Subspecies Nilotica (Kotschy), A.N. Henry et. al. in Ethiopia - Gurmu Benti, Deribe (2005)
The ecology and the phenotypic variations of Vitellaria paradoxa (Gaertner f.), a multipurpose tree, highly valued for its oil was studied in Gambella region: Ethiopia. The objective of the study was to examine the ecology and the phenotypic variations between and within the natural population of Vitellaria paradoxa. The sections under ecological studies were done through inventory of the woodland based on random sampling method, in green house and in laboratories while the phenotypic variations were analyzed based on morphological traits. Results from population survey of 46 ha of woodland consisting of 230 quadrats showed that Vitellaria paradoxa accounted for 9.9% of the total trees and its basal area was estimated at 1.68 m2 ha -1, representing an 30.15% of the total cover. There were significant differences, at P<0.05, in terms of mean diameter at breast height, height and basal area between the populations. The total stocking rate was estimated only at 18 trees ha-1 and estimation of the diameter class of the species showed that 48.54% of the trees had diameters lying above the mean. The recruitments were estimated at 22 seedlings ha-1 and the species demography was also not encouraging as the ratio between the matured trees and the recruitments were approximately equal (1:1). There were also no viable seeds of Vitellaria paradoxa found in the soil seed bank. The soil seed bank was dominated by grasses (43%) and sedge (22%) and there was no correspondence between the seed bank regenerations and the natural populations particularly for trees and shrubs. The regeneration trend showed that the population of Vitellaria was threatened.